2015
DOI: 10.1002/eji.201445307
|View full text |Cite
|
Sign up to set email alerts
|

F pocket flexibility influences the tapasin dependence of two differentially disease‐associated MHC Class I proteins

Abstract: The human MHC class I protein HLA-B*27:05 is statistically associated with ankylosing spondylitis, unlike HLA-B*27:09, which differs in a single amino acid in the F pocket of the peptide-binding groove. To understand how this unique amino acid difference leads to a different behavior of the proteins in the cell, we have investigated the conformational stability of both proteins using a combination of in silico and experimental approaches. Here, we show that the binding site of B*27:05 is conformationally disor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(66 citation statements)
references
References 72 publications
4
60
0
2
Order By: Relevance
“…The above presented concept of the relevance of the conformational landscape of a ‘receptor' molecule on downstream pathways might not only be applicable to the closely related tapasin-catalysed peptide loading of MHC class I molecules42434445 but is also known to other biological systems: The energy landscape of G-protein coupled receptors that strongly impacts activation pathways has been shown to depend on the individual receptor/ligand complex46 and as shown in this study, ligands might not act on the crystallizable ground states but on low-populated excited states47. For example, an order-to-disorder transition of two helical segments in the rhodopsin effector Gαi1 has been postulated and mutations that affect the thermodynamic stability of this region were shown to have a large effect on GDP release48.…”
Section: Discussionmentioning
confidence: 99%
“…The above presented concept of the relevance of the conformational landscape of a ‘receptor' molecule on downstream pathways might not only be applicable to the closely related tapasin-catalysed peptide loading of MHC class I molecules42434445 but is also known to other biological systems: The energy landscape of G-protein coupled receptors that strongly impacts activation pathways has been shown to depend on the individual receptor/ligand complex46 and as shown in this study, ligands might not act on the crystallizable ground states but on low-populated excited states47. For example, an order-to-disorder transition of two helical segments in the rhodopsin effector Gαi1 has been postulated and mutations that affect the thermodynamic stability of this region were shown to have a large effect on GDP release48.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, increasing experimental and computational evidence of wild type (WT) and mutant MHC complexes over the past years incontestably revealed that changes in conformational dynamics in MHC proteins have to accompany peptide loading and exchange (22, 4046). …”
Section: Structural Variations In Mhc Complexesmentioning
confidence: 99%
“…In such simulations, peptide-free class I protein is modeled from the crystal structure by deleting the atoms of the bound peptide. In the absence of peptide, an increased conformational flexibility of the F pocket region was observed for several allelic variants (HLA-A*02:01, HLA-B*44:02, HLA-B*44:05, HLA-B*27:05, HLA-B*27:09, H-2D b , and H-2K b ) (9, 15, 21, 22, 6971). Longer simulations of chicken and human class I allotypes showed increased global motion in the peptide-free form when compared to the peptide-bound proteins (72, 73).…”
Section: Dynamics Of Peptide-free Mhc Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…These data can also be interpreted on the basis of recent biophysical and computational analyses. Indeed, several studies have described an enhanced degree of flexibility and disorder of B*2705 and B*2704 peptide-binding cleft in comparison to that of B*2706 and B*2709 alleles [45][46][47]. This would influence the tapasin dependence, the folding dynamics and the stability of HLA-peptide complexes overall [46].…”
Section: Introductionmentioning
confidence: 99%